Sustainable agriculture through seaweed biostimulants: a two-year study demonstrates yield enhancement in pepper and eggplant - Staykov, Nikola; Kanojia, Aakansha; Lyall, Rafe; Ivanova, Valentina; Alseekh, Saleh; Petrov, Veselin; Gechev, Tsanko (Frontiers in Plant Science, 2025)
Global climate change and unsustainable agricultural practices have intensified the need for eco-friendly strategies to improve crop resilience and productivity. This study evaluates the efficacy of a seaweed-based biostimulant derived from Ascophyllum nodosum extract (ANE) in enhancing yield-related traits in pepper (Capsicum annuum) and eggplant (Solanum melongena) under open-field conditions over two consecutive years. Foliar applications of ANE were performed during early flowering stages, and plant performance was assessed using yield measurements, metabolomics, transcriptomics, and elemental analyses. ANE application significantly increased total fruit yield, primarily through higher fruit numbers per plant and, to a lesser extent, increased fruit size/weight, with hints to these effects traced back to earlier developmental stages. Metabolomic analyses revealed that ANE treatment modulated primary metabolism, enhancing sugar and amino acid levels, nitrogen assimilation, and osmoprotection, which together supported improved fruit set and development. Transcriptomic profiling demonstrated consistent gene expression changes in pathways related to cell wall modification, stress response, and carbohydrate metabolism. Elemental analysis indicated a general nutrient dilution effect due to increased biomass, with the notable exception of magnesium, which was enriched in ANE-treated pepper fruits. These findings highlight the potential of ANE as a sustainable agricultural input to improve yield and quality in vegetable crops while supporting environmentally responsible farming practices.